WUJUD MORAL ISLAM DALAM LEMBAH KEHIDUPAN (KUMPULAN CERITA PENDEK) KARYA M. HUSSEYN UMAR DENGAN PENDEKATAN PRAGMATIK - Kingkin Fadhilah Fitrianna; YB Maridja (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study was to describe (1) the characters, characterizations, and background, (2) a form of Islamic morals in the Lembah Kehidupan (Collection of Short Stories) by M. By Husseyn Umar. The research is a qualitative research. The research data is qualitative data in the form of dialogue phrases, sentences, paragraphs or units in Lembah Kehidupan (Collection of Short Stories) by M. Husseyn Umar. The primary data source is the Lembah Kehidupan (Collection of Short Stories) by M. Husseyn Umar issued by PT. Fikahati Aneska cooperation with BANI Arbitration Centre in 2013. The research instrument is the researchers themselves are equipped with a set of theories about the characters, characterizations, background, theoretical form of Islamic moral and pragmatic theory of literature. Data collection methods using a reading method, record, and library. Analysis data was conducted using the qualitative descriptive technique. The results of the study are as follows. (1) Figures, characterizations, and background in the Lembah Kehidupan (Collection of Short Stories) consists of, the main character is Hamid, he is a hard-working (short story